The Persistency of Public Debt - Felix Rösel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper shows that geographic patterns in public debt can be highly persistent despite drastic external shocks. I compare pre-Nazi debt in 60 districts and 132 large cities of the German Reich with current local government debt. German local government debt completely defaulted after WWII. I find that 1932 and 2012 debt is highly correlated in cities which saw a re-installation of their pre-Nazi mayor by the Allies in 1945. Comparable cities without personnel continuity do not exhibit a robust correlation. Intertemporal personnel links thus constitute a main channel through which to explain long-term persistency in public finance.
Keywords: H63; H74; N94; 330